Perception and utilization of mammography among women in selected Primary health centres in Ibadan North Local Government, Oyo state (2018)
Mammography is the most effective screening tools for early detection of breast cancer, but studies indicate low utilization. Yet, many women die from breast cancer in Nigeria with majority of them presenting in the late stage of the disease. This study was therefore designed to assess the perception and utilization of mammography in prevention of breast cancer among women, in selected primary health centres in Ibadan North Local Government Area, Oyo State, Nigeria. This descriptive cross-sectional study was carried out among 219 women who consented and were selected using purposive sampling technique. A structured validated questionnaire was used for data collection. Data were analysed using SPSS, version 20 and hypotheses were tested using chi-square at p=0.05. Findings from the study showed that majority of the respondents (50.2%) were in the age range of 26 35 years. Most 160 (73.1) are aware of Mammography and 57.1% of the women affirmed that mammography helps them to understand breast cancer. Only 4.6 % of the respondents had utilized mammography. In addition, many 130 (59.4%) affirmed that cost was a major factor responsible for non-utilization of mammography, others factors are lack of social support 122(55.7), lack of encouragement 115(52.5), not prescribed 84(38.4) and these also had significant statistical association with utilization of Mammography (p<0.05). This study revealed that mammography is being under utilised therefore there is need for more sensitization by stakeholders. Moreover, policy makers should look into ways of subsidizing the cost of mammography in order to encourage utilization. This will help in reducing morbidity and mortality to breast cancer among women in Ibadan North Local Government area.